REPRESENTAMEN, OBJECT, AND INTERPRETANT OF COLGATE VIDEO ADVERTISEMENT - Shafirany Arafah Zahra Hasry; R. Myrna Nur Sakinah (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
Advertising media has expanded across various media channels, including television, radio, print, online, and social media. Each channel has its unique dynamics and challenges. An integral part of advertising research is delving into consumer psychology. It investigates how ads affect consumers, influence their decision-making, advertising help capture closer old and new cultural denotation and invest them in consumer goods which can be more accessible to consumers, and trigger emotions or reactions. As in this research, the researcher try to find the meanings of sign through video advertisement. This issue primarily revolves around the utilization of signs, the emergence of images, and the dissemination of information, encompassing meaning and the potential impact of advertising on people's perception Signs in social semiotic terms, In this research, the researcher uses Charles Sanders Peirce’s theory of signs to uncover meanings in signs that included in Colgate video advertisement. In the context of advertising, signs are commonly associated with various displays, often incorporating words and images, to announce the location and nature of businesses, especially in the term of luxury goods for upper middle class, that’s why the researcher expand the broader meaning of semiotics through Thorstein Veblen’s theory of luxury. Media periklanan telah berkembang di berbagai saluran media, termasuk televisi, radio, media cetak, online, dan media sosial. Setiap saluran memiliki dinamika dan tantangan yang unik. Bagian integral dari riset periklanan adalah mempelajari psikologi konsumen. Ini menyelidiki bagaimana iklan mempengaruhi konsumen, mempengaruhi pengambilan keputusan mereka, periklanan membantu mendekatkan denotasi budaya lama dan baru dan menginvestasikannya pada barang-barang konsumsi yang lebih mudah diakses oleh konsumen, dan memicu emosi atau reaksi. Seperti pada penelitian ini, peneliti mencoba mencari makna tanda melalui video iklan. Permasalahan ini terutama berkisar pada pemanfaatan tanda, kemunculan gambar, dan penyebaran informasi, meliputi makna dan potensi dampak iklan terhadap persepsi Masyarakat, serta tanda dalam istilah semiotik sosial. Dalam penelitian ini, peneliti menggunakan teori Charles Sanders Peirce. tanda-tanda untuk mengungkap makna tanda-tanda yang terdapat dalam iklan video Colgate. Dalam konteks periklanan, tanda umumnya diasosiasikan dengan berbagai tampilan, seringkali disertai kata-kata dan gambar, untuk mengumumkan lokasi dan sifat usaha, khususnya dalam hal barang mewah untuk kelas menengah ke atas, oleh karena itu peneliti memperluas makna yang lebih luas dari iklan. semiotika melalui teori kemewahan Thorstein Veblen.